The Influence of Knowledge on Differences in the Level of Understanding of the Community of Teluk Sentosa about Sharia and Conventional Bank Products - Sri Ratna Devi; Nasution, Annio Indah Lestari; , Ahmad Syakir (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine the effect of knowledge on differences in the level of understanding of the people of Teluk Sentosa about Islamic and Conventional Bank products. The population in this study were all people of Teluk Sentosa totaling 6,865 people. While the sample of this study is to take 10% of the total population of 99 people. This study uses quantitative methods with data collection using the Likert scale method. The data analysis technique through the IBM SPSS statistical program 25. The results of this study indicate that Knowledge has a significant effect on the level of understanding of the people of Teluk Sentosa about Islamic and Conventional Bank products.